Design and formulation of ministerial regulation on remote and hybrid work to enhance employment for individuals with physical and sensory disabilities - Qistina Syakira; Ilaria Sekar Ailsa; Vania Athalia Lumban Tobing (Green Governance: Exploring Politics, Social Justice, and the Environment, 2025)
Background: People with physical and sensory disabilities remain highly vulnerable to discrimination and exclusion, particularly in the employment sector. Their limited workforce participation is often caused by systemic barriers, lack of accessibility, and insufficient inclusive policy frameworks. This study aims to assess the urgency and regulatory design needed to support remote working and hybrid office systems through the Regulation of the Minister of Manpower and the Regulation of the Minister for Administrative and Bureaucratic Reform. These systems are seen as strategic efforts to enhance inclusive employment for persons with disabilities. Methods: This research applies a normative juridical method, utilizing statutory, conceptual, and comparative legal approaches. Relevant laws and regulations are analyzed alongside comparative studies from Italy, Spain, and England, which have advanced inclusive employment practices. Findings: The study finds that regulatory reforms must be grounded in principles of justice, inclusivity, accessibility, and non-discrimination. By adopting flexible work arrangements through strong legal frameworks, the government can provide more equitable opportunities for individuals with physical and sensory disabilities. The integration of these values into ministerial regulations is crucial for fostering an inclusive working environment and improving labor absorption. Conclusion: Inclusive and well-formulated regulations on remote and hybrid working systems are essential to accelerating equal employment access for persons with physical and sensory disabilities in Indonesia. Novelty/Originality of this article: This study offers an original legal framework proposal that integrates inclusive employment values with flexible work systems, contributing a new perspective to disability-focused regulatory reform in Indonesia.